Integrasi Laporan Keuangan dan Dana Kampanye Partai Politik - Metrina - Tosika; Khairul Fahmi; Asrinaldi Asrinaldi (Jurnal Administrasi dan Kebijakan Publik, 2020)
This research is motivated by the financial statements of political parties and campaign funds for Political Parties Election Contestants in Indonesia which intersect but are not integrated into one source of public information. Political party reforms that have not yet occurred have an impact on the financial arrangements of political parties that are not detailed, transparent, and accountable. So we need the formula to unify all financial statements of political parties in an application or information system that contains information on revenue and expenditure from all financial sources of each political party. This is because providing access to political finance is crucial to the quality of elections and democracy. The purpose of this study is to illustrate the need for integration of political party financial reports and campaign funds in an information system that is widely accessible to the public. The research method used is a literature study. In this study it can be concluded that the integration of political parties' financial statements is necessary because voter references to the finances of political parties and candidates in the previous elections can affect the quality of the level of participation in the next election.